L’intervention en maison d’hébergement auprès des femmes immigrantes victimes de violence conjugale : une analyse intersectionnelle des pratiques - Castro-Zavala, Sastal (Canadian Social Work Review, 2020)
Cet article présente les résultats d’une recherche qualitative qui explore, à partir de la perspective féministe intersectionnelle, les points de vue d’intervenantes des maisons d’hébergement du Québec sur leurs pratiques d’intervention auprès des femmes immigrantes victimes de violence conjugale, ainsi que sur les facteurs qui influencent ces pratiques. La collecte de données a été réalisée par le biais de cinq groupes focalisés répartis dans quatre régions du Québec : Montréal, Québec, Sherbrooke et Gatineau. Trente-trois intervenantes issues de maisons d’hébergement pour femmes violentées ont participé à la recherche. L’analyse des résultats a permis de dégager deux thèmes principaux autour desquels s’articulent les discours des intervenantes au sujet de leurs pratiques : la nature de ces pratiques en contexte de diversité culturelle et les facteurs qui les modulent.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; discipline; femmes* immigrantes; intersectionnalité; intervention sociale; maisons d'hébergement; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; travail social; violences; violences conjugales; étude qualitative

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Là où je me terre: roman - Dawson, Caroline (Les éditions du remue-ménage, 2020)
« Valparaíso, décembre 1986, tremblement de terre entre les quatre murs d'une maison. Un homme et une femme annoncent à leurs enfants qu'il faut tout laisser derrière et fuir le Chili de Pinochet. C'est Noël, la petite Caroline a sept ans et elle aura la nausée durant tout le voyage. La fillette atterrit à Montréal. En plus de la neige dehors, il y a le tapis rouge vin de l'hôtel Ramada qui accueille les personnes réfugiées en attente de papiers. Il y a aussi Passe-Partout qui semble s'adresser à elle à travers le téléviseur. Après le premier appartement à Montréal-Nord, la classe d'accueil de madame Thérèse qui lui apprend le français, les enfants qui se moquent de ses cheveux et de sa boîte à lunch, la misère des rues d'Hochelaga, il y aura tout ce temps passé dans les banques où ses parents font des ménages. Entre l'exil, les fantômes du passé et le jeu des différences, la petite Caroline camouflera sa furieuse envie de vivre pour ne plus détonner et devenir une immigrante modèle. Mais comment apprend-on à ne plus s'effacer? Peut-on embrasser une nouvelle culture sans renier ses origines? Lumineux et vivant, Là où je me terre sonde la possibilité d'aimer et de lutter sans ne plus avoir à fuir. »
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; intersectionnalité; inégalités; justice sociale; lit301N; littérature; maternité; montréal; premier cycle; périodes historiques; québec; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; écriture des femmes*

Les pratiques artistiques des personnes sourdes ou handicapées au Canada - Leduc, Véro; Boukala, Mouloud; Rouleau, Joëlle; Louw, Aimee; McAskill, Ashley; Théroux, Catherine; Heussaff, Sarah; Grenier, Line; Bernier, Mélina; Bouscatier, Shandi; Marcelli, Élodie; Parent, Laurence; et al. (Conseil des arts du Canada, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; audisme; canada; capacitisme; féminisme décolonial; intersectionnalité; outils; personnes handicapé.e.s*; personnes sourdes; pour des recherches en milieux de pratiques; périodes historiques; représentations culturelles; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

L’intervention féministe sous l’influence de l’intersectionnalité : enjeux organisationnels et communicationnels au sein des organismes féministes au Québec - Marchand, Isabelle; Corbeil, Christine; Boulebsol, Carole (Communiquer. Revue de communication sociale et publique, 2020)
Au Québec, l’intervention féministe se déploie significativement au milieu des années 1970 et se présente comme une alternative, à la fois thérapeutique et politique, aux thérapies traditionnelles dans le champ de la santé mentale et de la lutte contre les violences sexistes, pour soutenir les femmes et défendre leurs droits. Elle repose, entre autres, sur la conscientisation et la reprise de pouvoir, à la fois individuelle et collective, dans une société marquée par la discrimination sexiste. Plus récemment, la popularité de l’intersectionnalité, comme cadre d’analyse théorique, politique et pratique, amène les intervenantes féministes francophones à adopter un regard critique sur leurs approches et leurs postures, en considérant notamment l’imbrication du sexisme avec d’autres formes d’oppression comme le racisme. À partir de plusieurs travaux menés au cours des dernières années auprès de praticiennes, les autrices proposent de réfléchir au développement récent de l’intervention féministe sous l’influence de l’intersectionnalité. Cet article suggère quelques pistes d’analyse sur les enjeux organisationnels et relationnels avec lesquels les groupes et les intervenantes doivent composer dans un contexte social et d’intervention qui se complexifie.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; femmes* racisées; histoire et politique; intersectionnalité; intervention féministe; maisons d'hébergement; militance; organisations féministes; périodes historiques; québec; recherche en milieux de pratique; ressource en ligne; régions géographiques; thématiques; travail

Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé